2022
DOI: 10.3389/fpsyt.2022.894939
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Psychiatric Emergencies in Two Different Settings: Emergency Room and Community Mental Health Service

Abstract: BackgroundThe SARS-CoV-2 pandemic caused a public health emergency with profound consequences on physical and mental health of individuals. Emergency Rooms (ER) and Community Mental Health Services (CMHS) played a key role in the management of psychiatric emergencies during the pandemic. The purpose of the study was to evaluate urgent psychiatric consultations (UPCs) in the ERs of the General Hospitals and in the CMHS of a Northern Italian town during the pandemic period.MethodsThis monocentric observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Although it is quite intuitive that an emergency such as a pandemic causes an increase in acute psychopathological distress and that adaptation to a prolonged critical period depends on resilience and coping strategies to continue to function well despite adverse circumstances [ 14 ], it is important to examine the impact of the persistence of the pandemic on the mental health in young people. To date, several studies have focused on psychiatric emergencies during the COVID-19 pandemic and analyzed requests for psychiatric counseling in the Emergency Room (ER), but these were studies of adult populations [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is quite intuitive that an emergency such as a pandemic causes an increase in acute psychopathological distress and that adaptation to a prolonged critical period depends on resilience and coping strategies to continue to function well despite adverse circumstances [ 14 ], it is important to examine the impact of the persistence of the pandemic on the mental health in young people. To date, several studies have focused on psychiatric emergencies during the COVID-19 pandemic and analyzed requests for psychiatric counseling in the Emergency Room (ER), but these were studies of adult populations [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some mental health services were reorganized to include telepsychiatry (9)(10)(11). An Italian study indicated an increased demand for urgent psychiatric consultations predominantly for vulnerable groups like people living in psychiatric facilities (12). Following the first pandemic wave in early 2020, two more waves developed in the course of 2020 and 2021.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Another study reported that the reasons for urgent psychiatric consultations in the emergency pertained to aggressiveness, socio-environmental maladjustment, and psychiatric symptoms in organic disorder. [ 18 ] Another similar paper from Germany reported an increased frequency of patients with personality disorders but reduced presentations of affective disorders during the pandemic. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%